Chronobiological Aspects of the Heart Rhythm Disorders at the Change of Pulmonary Ventilation in Rat Model - Svorc, Pavol; Marossy, Alexander; Svorc, Pavol; Jr.; Gresova, Sona; Buzga, Marek; Fulton, Benjamin L. (IntechOpen, 2012)
None